(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A writer is identified based on the socio-topographical network and culture in which he belongs,as well as the customs, life, and language he employs in his writings. The Indian English authors of the1980s are totally accustomed to Western society, creating a distinct social and abstract heritage that islinked to life in India and abroad. The literature expresses individual lives, but it also portrays the totalhuman attitude toward society. In reality, literature shapes societal attitudes and draws the ideology andmentality of society. The writer’s viewpoint on society is crucial in preserving history, reflecting currentsociety, and projecting the future. The multi-cultural viewpoint of Vikram Seth’s writings is examined inthis article.